Antioxidant and acetylcholinesterase activities of three species of the family Lamiaceae (Bangladesh Journal of Botany, 2015)
Antioxidant and acetylcholinesterase inhibitory activity of the three species namely, Endostemon obtusifolius (E. Mey. ex benth.) N. E. Br, Plectranthus zuluensis (T. Cooke) and Tetradenia riparia (Hochst.) Codd. were evaluated. Maximum antioxidant activity was exhibited by E. obtusifolius (IC50 130 ?g/ml) followed by T. riparia (IC50 142 ?g/ml) and P. zuluensis (IC50 169 ?g/ml). Acetylcholinesterase inhibition (AChEI) was highest in P. zuluensis (IC50 290 ?g/ml) followed by E. obtusifolius (IC50 470 ?g/ml) and T. riparia (IC50 750?g/ml). The results suggest that these three species possess natural antioxidants and acetylcholinesterase inhibitors, which may be beneficial for the treatment of Alzheimers disease, that require high concentration of these compounds. DOI: http://dx.doi.org/10.3329/bjb.v43i3.21606 Bangladesh J. Bot. 43(3): 331-335, 2014 (December)